METABOLIC CONSEQUENCES AFTER UNDERGOING RESECTION OF THE PANCREAS - І. Novarchuk (Bogomolets National Medical University, 2015)
Resection pancreas is the only effective treatment for a number of malignancies biliopankreato- duodenal zone and complicated forms of chronic pancreatitis. Type 3 Diabetes is a major factor affecting the quality of life of patients who underwent resection of the pancreas. Cases of diabetes are 3 types depend on the type of surgery, degree of resection and software as abandoned gland tissue. In our study, was recorded a clear association of diabetes with 3 types of postoperative complications. We believe that rational surgical tactics, adequate preoperative preparation will certainly affect the reduction in the risk of developing diabetes type 3.